Applications of Danishefsky’s dienes in asymmetric Oxo-Diels-Alder reactions - Taheri kal Koshvandi, Afsaneh; Heravi, Majid M. (Tetrahedron: asymmetry, 2017)
[Display omitted] Applications of Danishefsky’s dienes in catalytic asymmetric hetero-Diels-Alder (AHDA) reactions or specifically, their asymmetric Oxo-Diels-Alder (AOxo-DA) reactions with appropriate dienophiles are highlighted in detail, including the preparation of catalysts with discussion from a mechanistic points of view. Danishefsky’s dienes are effective and useful compounds for the synthesis of optically active six-membered rings such as dihydropyrones, dihydropyridones and dihydropyrans. Due to the broad range of the overall subject, we have limited ourselves, to the recent developments in the utility of Danishefsky’s dienes in the reaction with carbonyl compounds (aldehydes, ketones and 1,2-dicarbonyl compounds) in asymmetric Oxo-Diels-Alder (AOxo-DA) reactions.